Surface Roughness Variation Across Polar Ice Deposit Boundaries on Mercury. Issue 11 (7th November 2022) - Deutsch, Ariel N.; Colaprete, Anthony; Heldmann, Jennifer L.; Elphic, Richard C.; Cannon, Kevin M.
Abstract: We analyze the surface roughness of five north polar craters on Mercury using 125 m/pixel Mercury Laser Altimeter data. Each crater hosts a polar deposit (PD) with a low‐reflectance surface. The PDs have distinct geologic contacts, enabling an analysis of roughness across deposit boundaries onto ice‐free portions of the host craters' floors. The low‐reflectance surfaces in Angelou, Despréz, and Ensor collocate with radar‐bright signatures consistent with the presence of several‐meters‐thick water‐ice deposits beneath their low‐reflectance surfaces. Subdued roughness in these three craters is consistent with the superposition of several meters of ice. The difference between roughness on and off their low‐reflectance surfaces is within one standard deviation (SD) of the results, but is found to be statistically significant, as indicated by K‐S and Mann‐U Whitney tests, and meaningful, as indicated by Cohen's d tests. There is no meaningful difference in Jiménez and Josetsu, two craters that lack strong radar‐bright signatures, consistent with the hypothesis that they do not host substantial water ice beneath their low‐reflectance surfaces and thus not all of Mercury's available cold traps are occupied by water ice. Analyzing the roughness of polar craters may provide insight into the presence/absence of thick volatile deposits, but higher‐resolution topography would be helpful given the high SD associated with roughness. Finally, we identify subdued roughness along three PDs that may be related to thick lag deposit margins or enhanced diffusive mixing along deposit edges. Roughness may provide new insight into surface characteristics of the ices and inform surface evolution models. Plain Language Summary: Many polar craters on Mercury host dark ices, some of which have strong radar signatures indicating there are thick water‐ice deposits just beneath the dark surface ice. Today, little is known about the ices' texture, which provides information about the ices' physical nature and modification history. We analyze the texture of five craters with dark ice deposits. Dark deposits with strong radar‐bright signatures are meaningfully less rough than neighboring ice‐free surfaces, suggesting water ice smooths the surface texture by filling in underlying topography. We do not observe a distinct smoothing at dark deposits without strong radar‐bright signatures, suggesting there are not thick water‐ice deposits beneath those dark surfaces. The variation in roughness measurements is statistically high, so acquiring new high‐resolution measurements of Mercury's polar deposits would help improve and expand this analysis. Some of the analyzed dark ices appear to be smoothest along their edges, suggesting the ice may be thickest at the edges, or small impacts that cause texture variations may disappear more quickly at the ice edges. Continuing to study the texture of polar ices could provide insight into the protective properties of the dark materials found on top of some of Mercury's ices. Key Points: Radar‐bright, low‐reflectance polar deposits are distinctly smoother than adjacent ice‐free floors in three craters on Mercury The superposition of several meters of radar‐bright water ice is likely responsible for the subdued roughness The roughness of two low‐reflectance polar deposits without strong radar‐bright signals and ice‐free floors are not meaningfully different